Aerosol Particles Generated by Coughing and Sneezing of a SARS-CoV-2 (COVID-19) Host Travel over 30 m Distance - Boris Gorbunov (Aerosol and Air Quality Research)
Abstract A fast-computational 3D model comprising fluid dynamics with heat transfer, mass transfer and diffusion of diluted species has been adapted and employed to evaluate dispersion of aerosol particles in various environments. Effects of convection flow, atmospheric diffusivity and humidity on evolution and travel distances of exhaled aerosol clouds by an infected person are modelled. The modelling clearly demonstrates how aerosol particle dispersion is influenced by weather and geometry of the environment. The results obtained demonstrate that aerosol particles of sizes from 10 µm to 100 µm that potentially can carry SARS-CoV-2 (COVID-19) viruses travel over 30 m in some atmospheric conditions. Modelling of the evolution of aerosol clouds generated by coughing and sneezing enables us to evaluate the deposition dose of aerosol particles in healthy individuals. In realistic weather scenarios viruses can be deposited in the respiratory tract of a healthy individual at up to 200 virus copies in several minutes. A metric based on aerosol particle (volume) size distribution and the ICRP lung deposition model is suggested.